Navigating the Standard-based Creative Arts Curriculum Challenges in Primary Schools: A Qualitative Exploration - Alhassan, Hamza; Essel, Harry Barton; Kquofi, Steve (International Journal of Education and Teaching Zone, 2025)
This study explores the challenges and coping strategies associated with implementing the Standard-Based Creative Arts Curriculum (SBC) in Ghanaian primary schools. Guided by an interpretivist paradigm, a qualitative case study approach was used to capture the lived experiences of teachers and headteachers from selected public and private schools. Data were collected from two headteachers and six classroom teachers through structured interviews. While the small sample size limits generalizability, it enabled an in-depth examination of practitioner perspectives. Findings reveal a range of institutional, pedagogical, and resource-related barriers to effective curriculum implementation, including inadequate training, lack of materials, insufficient instructional time, and limited policy prioritization of Creative Arts. Despite these constraints, teachers demonstrated resilience by improvising with local resources, adapting culturally relevant content, and engaging in peer collaboration. The study calls for systemic reforms in teacher training, curricular support, school leadership, and resource allocation. It advocates for greater inclusion of teacher voices in policy development, promotion of culturally responsive pedagogy, and future longitudinal, multi-stakeholder research to maintain quality and equality in Creative Arts education both now and in the future.